Thermal and Spectral Studies of Ni(II) and Cu(II) Complexes with Chloramphenicol - Guru, Pranay (Asian Journal of Chemistry, 2016)
Ni(II) and Cu(II) complexes with chloramphenicol have been synthesized and characterized. On the basis of elemental analysis and molar conductance, formulae Ni(L)MoO4·2H2O and Cu(L)MoO4·4H2O (L = chloramphenicol) have been suggested for the complexes under study. The geometries of the complexes have been proposed on the basis of magnetic moment, electron and infrared spectral data. TGA studies have also been carried out to know the pattern of their decomposition. The crystal system, lattice parameters, unit cell volume and number of molecules in it have been determined by X-ray diffraction data; various ligand field parameters like Dq, B, etc. have been evaluated. The aim of investigation is to study the coordination behaviour of Ni and Cu in the presence of MoO42− anion.